2019
DOI: 10.1108/ijopm-04-2018-0195
|View full text |Cite
|
Sign up to set email alerts
|

The next phase in servitization: transforming integrated solutions into modular solutions

Abstract: Purpose -The purpose of this paper is to identify integrated solutions business as the first generation of servitized offerings and modular solution offerings as the second development phase in servitization of original equipment manufacturers. This study examines how the servitized manufacturer, Kone, moves from integrated solutions to modular solutions business and develops the requisite capabilities to design, produce and implement modular solution offerings. Design/methodology/approach -The paper reports a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 100 publications
(163 reference statements)
1
75
0
7
Order By: Relevance
“…In particular, the emerging literature on digital servitization shows that digital technologies allow manufacturers to provide new value creation and value capture opportunities through monitoring, control, optimization, and autonomous functions (Gebauer et al, 2020;Kohtamäki et al, 2019;Paschou et al, 2020). In other words, digital technologies not only facilitate servitized business models (Arnold et al, 2016;Suppatvech et al, 2019;Vendrell-Herrero et al, 2017), such as outcome business models (Sjödin et al, 2020a;Visnjic et al, 2017) but also contribute to the development of emerging industrial digital platforms with opportunities for value creation and capture that go far beyond traditional products and services (Cenamor et al, 2017;Rajala et al, 2019;Wei et al, 2019). However, the industrial digital platform development has implications for industrial manufacturers.…”
Section: Digital Servitization and Industrial Digital Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the emerging literature on digital servitization shows that digital technologies allow manufacturers to provide new value creation and value capture opportunities through monitoring, control, optimization, and autonomous functions (Gebauer et al, 2020;Kohtamäki et al, 2019;Paschou et al, 2020). In other words, digital technologies not only facilitate servitized business models (Arnold et al, 2016;Suppatvech et al, 2019;Vendrell-Herrero et al, 2017), such as outcome business models (Sjödin et al, 2020a;Visnjic et al, 2017) but also contribute to the development of emerging industrial digital platforms with opportunities for value creation and capture that go far beyond traditional products and services (Cenamor et al, 2017;Rajala et al, 2019;Wei et al, 2019). However, the industrial digital platform development has implications for industrial manufacturers.…”
Section: Digital Servitization and Industrial Digital Platformsmentioning
confidence: 99%
“…Digital servitization is enabled by connecting installed bases of industrial assets and equipment to an industrial digital platform that provides aggregation of data and analytical capabilities for greater value creation and capture (Kiel et al, 2017;Paiola and Gebauer, 2020). Thus, previous research showed that digital servitization goes hand-in-hand with a platform approach (Cenamor et al, 2017;Leminen et al, 2020;Rajala et al, 2019;Wei et al, 2019). For instance, industrial digital platforms allow to connect various IIoT-enabled machines, collect operational and equipment data, and conduct cutting-edge analytics to provide advanced platform services, such as preventive maintenance, fleet management, or even site optimization (Kohtamäki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Services are obviously very different from physical products, and interfaces in modular service design can be, e.g., people and information (Voss & Hsuan, 2009), and it can generate market impact efficiently through innovative offerings by reusing and varying existing services (Tuunanen & Cassab, 2011). In service business, modularization can also significantly reduce transaction costs among key actors (Rajala et al, 2019).…”
Section: From Physical To Software Modularitymentioning
confidence: 99%
“…Advanced services focus on the capabilities provided by a product's performance in use (Baines & Lightfoot, 2014). To design advanced services, research suggests a modular design strategy (Davies, 2004;Rajala et al, 2019). Modularity is a method for managing complex products and services efficiently (Baldwin & Clark, 2000) and refers to the degree to which a system's components can be separated and recombined with ease (Schilling, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Findings contribute to modularity and servitization literature by expanding understanding of the interplay between firm boundaries and management of efficiency and flexibility in the context of modular product-centric advanced services. Previous modularity studies have focussed on low variety contexts, such as the design and provision of advanced services in the elevator industry (e.g., Rajala et al, 2019), or on the organisations production system and excluded variety introduced to the system by the customer (e.g., Salonen et al, 2018;Kohtamäki et al, 2020), allowing them to transpose the scientific approach to modular design from manufacturing to service. In this study a servitized organisation operating in a high variety environment responds to emergent customer requirements by making physical design changes to products already designed, produced and exchanged with the customer.…”
Section: Introductionmentioning
confidence: 99%